2021
DOI: 10.1007/s42832-021-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial residues as the nexus transforming inorganic carbon to organic carbon in coastal saline soils

Abstract: Soil inorganic carbon (SIC), including mainly carbonate, is a key component of terrestrial soil C pool. Autotrophic microorganisms can assimilate carbonate as the main or unique C source, how microorganisms convert SIC to soil organic carbon (SOC) remains unclear. A systematic field survey (n = 94) was performed to evaluate the shift in soil C components (i.e., SIC, SOC, and microbial residues) along a natural salinity gradient (ranging from 0.5 ‰ to 19 ‰), and further to explore how microbial necromass as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recent evidences suggest that SOM formation is independent of chemical recalcitrance and that large proportions of SOM are directly derived from microbial‐derived necromass (Joergensen, 2018; Liang et al, 2017). In this study, we collected data of microbial residue C in whole coastal wetlands of China (Shao et al, 2022; Q. Li, Z. Song, S. Xia, L. Guo, B. P. Singh, Y. Shi, W. Wang, Y. Luo, Y. Li, J. Chen, J. Zhang, S. Sun, & H. Wang, Unpublished), and compared the contribution of lignin and microbial necromass C to SOC accumulation in coastal wetlands at a broader scale (Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences suggest that SOM formation is independent of chemical recalcitrance and that large proportions of SOM are directly derived from microbial‐derived necromass (Joergensen, 2018; Liang et al, 2017). In this study, we collected data of microbial residue C in whole coastal wetlands of China (Shao et al, 2022; Q. Li, Z. Song, S. Xia, L. Guo, B. P. Singh, Y. Shi, W. Wang, Y. Luo, Y. Li, J. Chen, J. Zhang, S. Sun, & H. Wang, Unpublished), and compared the contribution of lignin and microbial necromass C to SOC accumulation in coastal wetlands at a broader scale (Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…Plant inputs stimulate the activity and size of the soil microbial community, which could enhance the nutrient cycle and reduce soil pH of saline-alkali soil (Li et al, 2022;Liu et al, 2022;Rathore et al, 2022). Microbial biomass and the resulting microbial necromass, part of which can be relatively recalcitrant, provides binders for aggregates that physically protect soil organic matters and improve soil structure (Bronick and Lal, 2005;Zhu et al, 2018;Zhu et al, 2020;Shao et al, 2022). In this study, MB increased in halophytes field, and the response showed a strong correlation with desalinization effect, which highlights the importance of microbes in the process of soil improvement during desalinization (Figure 6).…”
Section: Aboveground Accumulation and Rootsoil Interaction Of Desalin...mentioning
confidence: 99%
“…The importance of soil microbes in transforming plant-derived organic matter and in fostering the formation of soil organic matter (SOM) have gained widespread acceptance but has been largely overlooked as a primary pathway of SOM formation until recently (Bardgett et al, 2008;Heimann and Reichstein, 2008;Schimel and Schaeffer, 2012;Kallenbach et al, 2016;Lu et al, 2018;Zhu et al, 2020). The sequestration of SOM depends on microbial metabolic pathways, mainly involving the decomposition, transformation and sequestration of organic matter, which is ultimately determined by microbial species and community diversity (Benner, 2011;Ludwig et al, 2015;Liang, 2020;Shao et al, 2021;Wang et al, 2021a). Determining how the soil microbial community regulates C fluxes and therefore controls biogeochemical cycling and climate change is urgent (Bond-Lamberty et al, 2018).…”
Section: Introductionmentioning
confidence: 99%